1999
DOI: 10.1111/j.1572-0241.1999.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mutations of K- Ras in Gallbladder Mucosae and Gallbladder Carcinoma With An Anomalous Junction of The Pancreaticobiliary Duct

Abstract: These results suggest that the specific K-ras mutation in codon 12 (GGT to GAT) may contribute to the early stage of carcinogenesis in the gallbladder with AJPBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 17 publications
3
28
2
Order By: Relevance
“…In contrast, the AUPBD pathway is strongly associated with the K-ras mutation (Funabiki et al, 2009). The reported frequency of the K-ras mutation in GBC with AUPBD ranged from 50 to 83%, whereas the frequency without AUPBD ranged from 0 to 36% (Hanada et al, 1996;Matsubara et al, 1996;Iwase et al, 1997;Hanada et al, 1999). Our results are consistent with these findings, because there were no AUPBD patients among the Bolivian cases, and the frequency of the K-ras mutation in Bolivia was low (1 of 36, 2.8%).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the AUPBD pathway is strongly associated with the K-ras mutation (Funabiki et al, 2009). The reported frequency of the K-ras mutation in GBC with AUPBD ranged from 50 to 83%, whereas the frequency without AUPBD ranged from 0 to 36% (Hanada et al, 1996;Matsubara et al, 1996;Iwase et al, 1997;Hanada et al, 1999). Our results are consistent with these findings, because there were no AUPBD patients among the Bolivian cases, and the frequency of the K-ras mutation in Bolivia was low (1 of 36, 2.8%).…”
Section: Discussionsupporting
confidence: 88%
“…The current study showed a significantly higher incidence of K- ras mutation in GBC, similar to what has been described earlier [21,23,26,27]. This is an expected finding as K- ras mutation occurs late in gallbladder carcinogenesis when it becomes invasive.…”
Section: Discussionsupporting
confidence: 79%
“…These variations possibly suggest different behaviors of this cancer in various high-risk populations. None of the previous studies have found K- ras codon 12 mutations in normal gallbladder mucosa [21,23,26,27]. In the present study, K- ras mutation was detected in a single normal gallbladder tissue sample, which is difficult to explain and suggest that the patient might be at high risk.…”
Section: Discussioncontrasting
confidence: 47%
“…In accordance to a more recent study [21], the most frequent mutation was a G ! T transversion that results in substitution of glycine for valine.…”
Section: K-ras Oncogenesupporting
confidence: 88%
“…It has also been reported that K-ras mutation at codon 12 is associated with early stage gallbladder carcinoma with APBDJ than in that without APBDJ [30].…”
Section: K-ras Oncogenementioning
confidence: 98%